Actividad Antimicrobiana in vitro de extractos metánolicos y hexánicos de Turnera diffusa contra patógenos comunes de vías urinarias - Angulo Escalante, M. A.; Báez-Parra, K. M.; Soto-Beltrán, M.; López-Cuevas, O.; Basilio Heredia, J.; Alcaraz-Meléndez, L. (Revista Bio Ciencias, 2019)
Turnera diffusa Willd. ex Schult. is well known in traditional medicine as aphrodisiac, diuretic, hypoglycemic, tranquilizer and urinary tract antiseptic, here we focus on antiseptic effect. The goal of this study was to examine the high performance thin layer chromatography fingerprinting of methanolic and hexanic extracts of two varieties of Turnera diffusa Willd. ex Schult. and evaluate the antimicrobial activity of these extracts against main tract urinary pathogens. A chromatographic profile of the extracts was generated by chromatography. For the methanolic extract the mobile phase was composed of ethyl acetate, acetic and formic acids and water (100:11:11:27). On the other hand, hexane and acetic acid (7.2:2.9) were used for the hexanic extract. Antimicrobial activity and minimum inhibition concentration were evaluated by the disc diffusion method and microdilution method, respectively, against Klebsiella pneumoniae, Enterococcus faeccalis, Staphylococcus aureus, Escherichia coli and Candida albicans. The methanolic extract revealed the presence of bands from yellow to orange while the hexanic extract showed bands from blue to violet. In addition, different Rf's were shown allowing the identification and differentiation of damiana varieties. The results showed antibacterial and antifungal activities of both methanolic and hexanic extracts. This study demonstrated that the chromatography fingerprinting profile developed for methanolic and hexanic extracts are an appropriate tool for identifying the damiana varieties. Since Turnera diffusa var. diffusa and Turnera diffusa var. aphrodisiaca showed antimicrobial activity against urinary tract pathogenic species, confirming their medicinal use.